(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: The prevailing issue in the global healthcare sector is burnout syndrome, characterized by depersonalization, personal accomplishment, and emotional tiredness. Because their work is so demanding, physical therapists are prone to burnout. There is a dearth of studies on burnout among physical therapists in Karachi, Pakistan, even though it negatively impacts both professional and patient treatment. Methodology: A validated instrument for measuring burnout, the Maslach Burnout Inventory (MBI), will be employed to measure personal accomplishment, depersonalization, and emotional exhaustion. A structured survey form will used to gather data on perceived organizational support, job-related variables, and demographic traits. Descriptive statistics and sophisticated regression techniques will be used in conjunction with data analysis to uncover burnout drivers and investigate potential moderating factors. Result: 281 physiotherapists were evaluated with the Maslach Burnout Inventory-Human Services Survey, and high levels of burnout components, were found: emotional exhaustion(44.1%),depersonalization (35.2%), and lower personal accomplishment (34.5%). Chi-square analysis provided evidence of significant correlations between prevalence of burnout, employment sector, professional experience, and type of employment (p < 0.01), with full-time professionals and workers in public hospitals showing significantly higher burnout. In particular, full-time working physiotherapists had 2.15 times greater chances of reporting high emotional exhaustion than part-time working ones (OR = 2.15; 95% CI: 1.21–3.83). Correlation was found between positive relationships of high scores on emotional exhaustion items (r = 0.80) and between depersonalization indicators (r = 0.76), indicating uniform patterns of occupational stress. Neither gender nor age was found significantly related to overall burnout rates (p > 0.05). The results emphasize that organizational context and workload are substantial predictors of burnout among Karachi physiotherapists. Conclusion: A large number of physiotherapists in Karachi are suffering from severe emotional and psychological stress due to the prevalence of burnout syndrome. To prevent burnout, the study emphasizes the necessity of strong support networks, efficient task management, and ongoing professional development. Also conduct more research, especially longitudinal studies, to investigate causal linkages and create focused solutions.